CO2 separation mixed matrix composite membrane and preparation method thereof

By changing the structure of the bridge molecules, an amine-based polymer modified MOF material with excellent interfacial compatibility was prepared, which solved the problem that MOF fillers are prone to interfacial defects and small loads in the mixed matrix membrane, and achieved the preparation of a high-performance CO2 separation membrane.

CN119588191AActive Publication Date: 2025-03-11CHN ENERGY NEW ENERGY TECHNOLOGY RESEARCH INSTITUTE CO LTD +2
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411772554.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

In the prior art, MOF fillers are prone to interfacial defects in the mixed matrix membrane, and the load is small, making it difficult to achieve efficient and low-energy-consuming CO2 separation.

Method used

By changing the structure of the bridge molecules, an amine-based polymer modified MOF material with different interfacial compatibility was prepared, expanding its interfacial compatibility range with the amine-based polymer matrix to prepare high-performance CO2 separation hybrid matrix membranes.

Benefits of technology

Excellent interfacial compatibility between MOF and amine-based polymer matrix is ​​achieved, and the performance of CO2 separation membrane is improved, with CO2 permeability rate >1491 and CO2/N2 selectivity >134.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588191A_ABST
    Figure CN119588191A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of gas separation membrane materials, and discloses a CO2 separation mixed matrix composite membrane and a preparation method thereof. The method comprises the following steps: mixing an amino-containing MOF, a bridging ligand, a first solvent and an optional first catalyst, carrying out a first reaction, and separating a solid product from a first reaction product to obtain a pre-modified solid; mixing the pre-modified solid, a part of the amino polymer, a second solvent and an optional second catalyst for a second reaction, and separating a solid product from a second reaction product to obtain modified MOF; and mixing the modified MOF with water to obtain a mixture, mixing the mixture with the other part of the amino polymer, and blade-coating the mixture on a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer. The infiltration effect between particles in the CO2 separation mixed matrix membrane and the amido polymer is remarkable, no interface defect is generated, the MOF loading capacity is high, and the CO2 separation mixed matrix membrane has excellent carbon dioxide separation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of gas separation membrane material preparation, and in particular to a CO 2 Separation mixed matrix composite membrane and preparation method thereof. Background Art

[0002] In recent years, the global anomaly caused by greenhouse gas emissions has become increasingly serious, forcing researchers to turn their attention to advanced carbon dioxide separation technology. The development of energy-saving, efficient and environmentally friendly carbon dioxide separation technology is of great significance to improving the overall economic benefits of the carbon capture, utilization and storage (CCUS) process. As a new generation of carbon capture technology, membrane separation has the characteristics of easy integration, flexible operation and low ecological footprint. It is widely believed to have the potential to significantly reduce the cost and energy consumption of carbon capture. However, existing commercial polymer membranes are trapped in the trade-off between permeability and selectivity, and cannot achieve efficient and low-energy separation.

[0003] Mixed matrix membranes (MMMs) are currently rapidly developing separation membranes. They have been proven to effectively combine the advantages of nanofillers and polymers, breaking through the upper limit of traditional polymer membrane performance. However, its research still needs to focus on the core feature of "interaction between nanofillers and polymers". One of the key structural characteristics of this type of membrane is that there is a specific phase interface between the nanoporous material and the polymer matrix. The mismatched interaction between the two components will lead to abnormal attenuation of membrane performance. Metal-organic framework (MOF) materials have many precedents in the field of membrane separation. However, the rigidity and high crystallinity of MOF materials make it easy for them to form interface defects with the polymer matrix in mixed matrix membranes. Therefore, MOF needs to be further modified to make it suitable as a CO separation membrane. 2 Separate the filler of the mixed matrix membrane and ensure that the filler is sufficient and stable in the polymer matrix.

[0004] Many efforts have been made to reduce interfacial defects. Post-modification of nanofillers (mainly MOFs or COFs with active reaction sites) and introduction of a third component to regulate the binary interface have been proven to be feasible. Among them, grafting polymers homologous to the matrix onto nanofillers through crosslinkers is a convenient and representative modification method. Therefore, exploring a general method to prepare amino-based polymer-modified MOF materials using different bridging ligands is a key issue that needs to be studied at present. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems in the prior art that adding MOF fillers to mixed matrix membranes is prone to interface defects and the MOF loading is small, and a CO 2Separation mixed matrix composite membrane and preparation method thereof, the method can obtain amine-based polymer modified MOF materials with different interface compatibilities by changing the structure of bridging molecules, can expand the interface compatibility range between amine-based polymer modified MOF and amine-based polymer matrix and can be used to prepare high-performance CO 2 Isolation of mixed matrix membranes.

[0006] In order to achieve the above object, the present invention first provides a CO 2 A method for preparing a separation mixed matrix composite membrane, the method comprising the following steps:

[0007] (1) mixing an amine-containing MOF, a bridging ligand, a first solvent, and an optional first catalyst and performing a first reaction, separating a solid product from the first reaction product to obtain a pre-modified solid;

[0008] (2) mixing the pre-modified solid obtained in step (1), a portion of the amino polymer, a second solvent and an optional second catalyst to conduct a second reaction, separating a solid product from the second reaction product to obtain a modified MOF;

[0009] (3) Mixing the modified MOF obtained in step (2) with another portion of the amino polymer and coating the mixture on a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer to obtain CO 2 Separation of mixed matrix composite membranes.

[0010] Preferably, in step (1), the MOF is selected from at least one of UIO series MOF, MIL series MOF and ZIF series MOF.

[0011] Preferably, the MOF is selected from UIO-66-NH 2 、CAU-1(Al)-NH 2 、MIL-53(Al)-NH 2 、MIL-101(Cr)-NH 2 、MIL-68(In)-NH 2 、MIL-101(Fe)-NH 2 、MIL-101(Al)-NH 2 、MIL-125(Ti)-NH 2 and ZIF-8-NH 2 At least one of .

[0012] Preferably, in step (1), the bridging ligand is selected from at least one of a diepoxide molecule, a dicarboxylic acid molecule and a dialdehyde molecule.

[0013] Preferably, the bridging ligand is selected from at least one of diepoxybutane, polyethylene glycol diglycidyl ether, oxalic acid, malonic acid, succinic acid, glutaric acid, glyoxal, terephthalaldehyde, glutaraldehyde and 4,4-biphenyldicarboxaldehyde.

[0014] Preferably, in step (1), the molar ratio of the amine group in the MOF to the bridging ligand is 1:2-5.

[0015] Preferably, in step (1), the first solvent is a polar solvent and / or a polar solvent.

[0016] Preferably, the first solvent is selected from at least one of water, ethanol, dimethylformamide and tetrahydrofuran.

[0017] Preferably, the first catalyst is selected from at least one of acetic acid, formic acid and propionic acid.

[0018] Preferably, the weight ratio of the first catalyst to the first solvent is 0.01-0.5:100.

[0019] Preferably, in step (1), the conditions of the first reaction include: reaction temperature of 40-80° C., and reaction time of 1-6 h.

[0020] Preferably, in step (2) and step (3), the amino polymer is a branched and / or linear amino polymer.

[0021] Preferably, the amine-based polymer is selected from at least one of polyvinylamine, polyethyleneimine and polypropyleneamine.

[0022] Preferably, in step (2), the weight ratio of the pre-modified solid to the portion of the amino polymer is 1-3:1.

[0023] Preferably, in step (2), the second solvent is an ethanol aqueous solution.

[0024] Preferably, the concentration of the ethanol aqueous solution is 30-80wt%.

[0025] Preferably, the second catalyst is selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide and triethylamine.

[0026] Preferably, the weight ratio of the second catalyst to the second solvent is 0.01-0.8:100.

[0027] Preferably, in step (2), the reaction conditions are: reaction temperature is 30-60° C., and reaction time is 0.5-4 h.

[0028] Preferably, in step (3), the weight ratio of the modified MOF to the other part of the amino polymer is 30-60:100.

[0029] The second aspect of the present invention discloses a CO prepared by the method described above. 2 Separation of mixed matrix composite membranes.

[0030] The CO of the present invention 2 Preparation method of separation mixed matrix composite membrane by using 2 The bridging ligand of the reactive group connects the amine-containing MOF and the amine-based polymer. By changing the structure of the bridging ligand, amine-based polymer-modified MOF materials with different interfacial compatibilities can be obtained, thereby expanding the interfacial compatibility range between the amine-based polymer-modified MOF and the amine-based polymer matrix and being used to prepare high-performance CO 2 The mixed matrix membrane separation method is simple to operate, low in cost, highly repeatable, and has good application prospects.

[0031] The CO of the present invention 2 The particles in the separation mixed matrix membrane have smooth surface morphology, uniform phase interface, no interface defects, and a high MOF loading, thereby 2 Mixed matrix membranes have excellent carbon dioxide separation performance. 2 Permeation rate>1491,CO 2 / N 2 Selectivity>134. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 CO prepared in Examples 1-3 and Comparative Example 1 2 Atomic force microscopy images of separated mixed matrix composite membranes. DETAILED DESCRIPTION

[0033] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0034] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0035] The CO of the present invention 2The method for preparing the separation mixed matrix composite membrane comprises the following steps:

[0036] (1) mixing an amine-containing MOF, a bridging ligand, a first solvent, and an optional first catalyst and performing a first reaction, separating a solid product from the first reaction product to obtain a pre-modified solid;

[0037] (2) mixing the pre-modified solid obtained in step (1), a portion of the amino polymer, two solvents and an optional second catalyst to carry out a second reaction, separating a solid product from the second reaction product to obtain a modified MOF;

[0038] (3) Mixing the modified MOF obtained in step (2) with another portion of the amino polymer and coating the mixture on a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer to obtain CO 2 Separation of mixed matrix composite membranes.

[0039] In the present invention, in step (1), the MOF may be at least one of a UIO series MOF, a MIL series MOF and a ZIF series MOF.

[0040] In a more preferred embodiment, the MOF is UIO-66-NH 2 、CAU-1(Al)-NH 2 、MIL-53(Al)-NH 2 、MIL-101(Cr)-NH 2 、MIL-68(In)-NH 2 、MIL-101(Fe)-NH 2 、MIL-101(Al)-NH 2 、MIL-125(Ti)-NH 2 and ZIF-8-NH 2 At least one of the following, most preferably UIO-66-NH 2 In these preferred embodiments, when the MOF is of the above type, the prepared modified MOF is 2 The separation mixed matrix composite membrane has better interfacial compatibility.

[0041] In the present invention, in step (1), the bridging ligand may be at least one of a diepoxy molecule, a dicarboxylic acid molecule and a dialdehyde molecule, preferably a diepoxy molecule. In the present invention, when the bridging ligand is of the above type (especially the preferred type), the prepared modified MOF is 2 The mixed matrix composite membranes have excellent interfacial compatibility.

[0042] In a more preferred embodiment, the bridging ligand is at least one of diepoxybutane, polyethylene glycol diglycidyl ether, oxalic acid, malonic acid, succinic acid, glutaric acid, glyoxal, terephthalaldehyde, glutaraldehyde and 4,4-biphenyldicarboxaldehyde, and diepoxybutane is most preferred. In these preferred embodiments, when the bridging ligand is of the above type, the prepared modified MOF is 2 The separation mixed matrix composite membrane has better interfacial compatibility.

[0043] In the method of the present invention, in step (1), the molar ratio of the amine group in the MOF to the bridging ligand can be 1:2-5, preferably 1:2-3. In these embodiments, when the molar ratio of the amine group in the MOF to the bridging ligand is within the above range (especially within the preferred range), the prepared CO 2 The separation mixed matrix composite membrane has better carbon dioxide selectivity.

[0044] In the present invention, in step (1), the first solvent may be a polar solvent and / or a polar solvent. In a preferred embodiment, the first solvent is at least one of water, ethanol, dimethylformamide and tetrahydrofuran. In the present invention, when the first solvent is of the above type (especially the preferred type), the reaction activity and grafting rate of the MOF and the bridging ligand in the prepared pre-modified solid are higher.

[0045] In the present invention, the first catalyst may be at least one of acetic acid, formic acid and propionic acid, preferably acetic acid. In the present invention, when the first catalyst is of the above type (especially the preferred type), the reaction activity and grafting rate of the MOF and the bridging ligand in the prepared pre-modified solid are higher.

[0046] In the method of the present invention, the weight ratio of the first catalyst to the first solvent can be 0.01-0.5: 100, preferably 0.1-0.5: 100. In the method of the present invention, when the weight ratio of the first catalyst to the first solvent is within the above range (especially within the preferred range), the reaction activity and grafting rate of the MOF and the bridging ligand in the prepared pre-modified solid are higher.

[0047] In the method of the present invention, in step (1), the conditions of the first reaction may include: a reaction temperature of 40-80°C, preferably 50-80°C; a reaction time of 1-6h, preferably 3-6h. In the method of the present invention, when the conditions of the first reaction are within the above range (especially within the preferred range), the reaction activity and grafting rate of the MOF and the bridging ligand in the prepared pre-modified solid are higher.

[0048] In some embodiments, the process of preparing the pre-modified solid may include: dispersing the MOF containing an amine group and the bridging ligand in a first solvent, adding a first catalyst and reacting at 40-80°C for 1-6 hours, filtering the obtained reaction product and washing it with ethanol until there is no obvious impurity, and removing most of the ethanol to obtain the pre-modified solid, wherein the molar ratio of the amount of the MOF containing an amine group to the bridging ligand is 1:2-5 based on the number of amine groups, and the weight ratio of the first catalyst to the first solvent is 0.01-0.5:100. When step (1) is implemented according to this embodiment, the prepared CO 2 The separation mixed matrix composite membrane has better carbon dioxide selectivity.

[0049] In the present invention, in step (2) and step (3), the amino polymer may be a branched and / or linear amino polymer. In a preferred embodiment, the amino polymer is selected from at least one of polyethyleneamine, polyethyleneimine and polypropyleneamine, preferably polyethyleneamine. In the present invention, when the amino polymer is of the above type (especially the preferred type), the prepared CO 2 The separation mixed matrix composite membrane has better carbon dioxide selectivity.

[0050] In the method of the present invention, in step (2), the weight ratio of the pre-modified solid to the part of the amino polymer can be 1-3: 1, preferably 1-2: 1. In these embodiments, when the weight ratio of the pre-modified solid to the part of the amino polymer is within the above range (especially within the preferred range), the reactivity and grafting rate of the bridging ligand to the amino polymer are higher.

[0051] In the present invention, in step (2), the second solvent is an ethanol aqueous solution. In a preferred embodiment, the concentration of the ethanol aqueous solution is 30-80 vol%. In the present invention, when the second solvent is the above-mentioned type (especially the preferred type), the reactivity and grafting rate of the bridging ligand and the amino polymer are higher.

[0052] In the present invention, the second catalyst can be at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide and triethylamine, preferably sodium carbonate. In the present invention, when the second catalyst is of the above type (especially the preferred type), the reactivity and grafting rate of the bridging ligand with the amino polymer are higher.

[0053] In the method of the present invention, the weight ratio of the second catalyst to the second solvent can be 0.01-0.8: 100, preferably 0.1-0.2: 100. In these embodiments, when the weight ratio of the second catalyst to the second solvent is within the above range (especially within the preferred range), the reactivity and grafting rate of the bridging ligand to the amino polymer are higher.

[0054] In the method of the present invention, in step (2), the reaction conditions may be: reaction temperature of 30-60° C., preferably 40-60° C.; reaction time of 0.5-4 h, preferably 2-4 h. In these embodiments, when the reaction conditions are within the above range (especially within the preferred range), the reactivity and grafting rate of the bridging ligand and the amino polymer are higher.

[0055] In some embodiments, the conditions for preparing the modified MOF may include: mixing the pre-modified solid and the part of the amino polymer in a second solvent, adding a second catalyst and reacting at 30-60°C for 0.5-4h, centrifuging the obtained reaction product and separating the solid product, washing the solid product with deionized water and ethanol, and vacuum drying at 60-90°C for 4-10h to obtain the modified MOF, wherein the weight ratio of the pre-modified solid to the part of the amino polymer is 1-3:1, and the weight ratio of the second catalyst to the second solvent is 0.01-0.8:100. When step (2) is implemented according to this embodiment, the prepared CO 2 The separation mixed matrix composite membrane has better carbon dioxide selectivity.

[0056] In the method of the present invention, in step (3), the weight ratio of the modified MOF to the other part of the amino polymer can be 30-60:100, preferably 30-50:100. In these embodiments, when the weight ratio of the modified MOF to the other part of the amino polymer is within the above range (especially within the preferred range), the prepared CO 2 The separation mixed matrix composite membrane has better carbon dioxide selectivity.

[0057] In some embodiments, the CO is prepared 2 The process of separating the mixed matrix composite membrane may include: ultrasonically dispersing the modified MOF in deionized water, blending the modified MOF dispersion and the other part of the amino polymer to obtain a mixed solution, wherein the weight ratio of the modified MOF to the other part of the amino polymer is 30-60:100, applying the mixed solution on a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and drying naturally at room temperature for 4-10 hours to obtain CO 2Separation mixed matrix composite membrane. When step (3) is implemented according to this embodiment, the prepared CO 2 The separation mixed matrix composite membrane has better carbon dioxide selectivity.

[0058] The CO of the present invention 2 In the separation mixed matrix composite membrane, the modified MOF has excellent interfacial compatibility with the amino polymer matrix, and the interfacial compatibility range between the amino polymer modified MOF and the amino polymer matrix can be expanded by changing the bridging ligand structure and used to prepare high-performance CO 2 Separation mixed matrix membrane, the CO 2 The particles in the separation mixed matrix membrane have smooth surface morphology, uniform phase interface, no interface defects, and a high MOF loading, thereby 2 Mixed matrix membranes have excellent carbon dioxide separation performance. 2 Permeation rate>1491,CO 2 / N 2 Selectivity>134.

[0059] The following examples further illustrate the CO 2 Separation mixed matrix composite membrane and preparation method thereof. The embodiments are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0060] The experimental methods in the following examples and comparative examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples and comparative examples, unless otherwise specified, are all commercially available.

[0061] Example 1

[0062] (1) 1 g of UIO-66-NH 2 and 0.9087 g of diepoxybutane (UIO-66-NH 2 The molar ratio of the amount of amine groups to the diepoxybutane is 1:3) dispersed in 40 mL of ethanol, 0.064 g of acetic acid (0.2 wt%) was added as a catalyst, and the reaction was carried out at 50° C. for 4 h. The obtained reaction product was filtered and washed with ethanol until there was no obvious impurity, and most of the ethanol was removed by suction to obtain a pre-modified solid;

[0063] (2) 1 g of the pre-modified solid obtained in step (1) was mixed with 2 g of polyethyleneamine in 40 mL of an ethanol aqueous solution containing 70 vol% ethanol, and 0.034 g of sodium carbonate (0.1 wt%) was added as a catalyst, and the obtained reaction system was reacted at 50° C. for 2 h. The obtained reaction product was then centrifuged to separate the solid product, and the solid product was washed with deionized water and ethanol, and vacuum dried at 80° C. for 6 h to obtain a modified MOF;

[0064] (3) 1 g of the modified MOF prepared in step (2) was ultrasonically dispersed in 10 mL of deionized water, and the modified MOF dispersion was blended with 2.25 g of polyvinylamine to obtain a mixed solution (the weight ratio of the modified MOF to the polyvinylamine was 44.44:100), and the mixed solution was scraped onto a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and naturally dried at room temperature for 6 h to obtain CO 2 Separation of mixed matrix composite membranes.

[0065] Example 2

[0066] (1) 1 g of UIO-66-NH 2 and 2.1853 g of malonic acid (UIO-66-NH 2 The molar ratio of the amount of malonic acid to the amount of amine groups is 1:5) dispersed in 40 mL of dimethylformamide, 0.07584 g of acetic acid (0.2 wt%) was added as a catalyst, and the reaction was carried out at 80° C. for 6 h. The obtained reaction product was filtered and washed with ethanol until there was no obvious impurity, and most of the ethanol was removed by suction to obtain a pre-modified solid;

[0067] (2) 1 g of the pre-modified solid obtained in step (1) was mixed with 2 g of polyethyleneimine in 40 mL of an ethanol aqueous solution containing 50 vol% ethanol, and 0.1074 g of sodium bicarbonate (0.3 wt%) was added as a catalyst. The obtained reaction system was reacted at 60° C. for 4 h, and the obtained reaction product was centrifuged to separate the solid product. The solid product was washed with deionized water and ethanol, and vacuum dried at 80° C. for 6 h to obtain a modified MOF;

[0068] (3) 1 g of the modified MOF prepared in step (2) was ultrasonically dispersed in 10 mL of deionized water, and the modified MOF dispersion was blended with 2.67 g of polyvinylamine to obtain a mixed solution (the weight ratio of the modified MOF to the polyvinylamine was 37.5:100), and the mixed solution was scraped onto a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and naturally dried at room temperature for 6 h to obtain CO 2 Separation of mixed matrix composite membranes.

[0069] Example 3

[0070] (1) 1 g of UIO-66-NH 2 and 0.840 g of glutaraldehyde (UIO-66-NH 2 The molar ratio of the amount of glutaraldehyde to the amount of amine groups is 1:2) dispersed in 40 mL of tetrahydrofuran, 0.3556 g of formic acid (0.1 wt%) was added as a catalyst, and the reaction was carried out at 60° C. for 3 h. The obtained reaction product was filtered and washed with ethanol until there was no obvious impurity, and most of the ethanol was removed by suction to obtain a pre-modified solid;

[0071] (2) 1 g of the pre-modified solid obtained in step (1) was mixed with 3 g of polyacrylamine in 40 mL of an ethanol aqueous solution containing 30 vol% ethanol, and 0.0366 g of sodium hydroxide (0.1 wt%) was added as a catalyst. The obtained reaction system was reacted at 40° C. for 3 h, and the obtained reaction product was centrifuged to separate the solid product. The solid product was washed with deionized water and ethanol, and vacuum dried at 80° C. for 6 h to obtain a modified MOF;

[0072] (3) 1 g of the modified MOF prepared in step (2) was ultrasonically dispersed in 10 mL of deionized water, and the modified MOF dispersion was blended with 2.43 g of polyethyleneimine to obtain a mixed solution (the weight ratio of the modified MOF to the polyethyleneimine was 41.18:100), and the mixed solution was scraped onto a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and naturally dried at room temperature for 6 h to obtain CO 2 Separation of mixed matrix composite membranes.

[0073] Example 4

[0074] (1) 1 g of MIL-53(Al)-NH 2 and 3.75 g of polyethylene glycol diglycidyl ether (Mw-600 g / mol) were dispersed in 40 mL of water (NH 2 -MIL-53(Al) and the polyethylene glycol diglycidyl ether are used in a molar ratio of 1:1.5 based on the number of amine groups), reacting at 40°C for 1 hour, filtering the obtained reaction product and washing it with ethanol until there are no obvious impurities, and removing most of the ethanol by suction to obtain a pre-modified solid;

[0075] (2) mixing 1 g of the pre-modified solid obtained in step (1) with 1 g of polyvinylamine in 40 mL of an ethanol aqueous solution containing 60 vol% ethanol, reacting the obtained reaction system at 60° C. for 0.5 h, centrifuging the obtained reaction product and separating the solid product, washing the solid product with deionized water and ethanol, and vacuum drying at 80° C. for 6 h to obtain a modified MOF;

[0076] (3) 1 g of the modified MOF prepared in step (2) was ultrasonically dispersed in 10 mL of deionized water, and the modified MOF dispersion was blended with 2.25 g of polyethyleneimine to obtain a mixed solution (the weight ratio of the modified MOF to the polyethyleneimine was 44.44:100), and the mixed solution was scraped onto a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and naturally dried at room temperature for 6 h to obtain CO 2 Separation of mixed matrix composite membranes.

[0077] Example 5

[0078] (1) 1 g of MIL-101(Cr)-NH 2 and 0.79 g of terephthalaldehyde (the MIL-101(Cr)-NH 2 The molar ratio of the amount of terephthalaldehyde to the amount of amine groups is 1:2.5) dispersed in 40 mL of ethanol, 0.16 g of propionic acid (0.5 wt%) was added as a catalyst, and the reaction was carried out at 70 ° C for 5 h, the obtained reaction product was filtered and washed with ethanol until there was no obvious impurity, and most of the ethanol was removed by suction to obtain a pre-modified solid;

[0079] (2) 1 g of the pre-modified solid obtained in step (2) was mixed with 1 g of polyacrylamine in 40 mL of an ethanol aqueous solution containing 75 vol% ethanol, and 0.2736 g of sodium carbonate (0.8 wt%) was added as a catalyst. The obtained reaction system was reacted at 50° C. for 2 h, and the obtained reaction product was centrifuged to separate the solid product. The solid product was washed with deionized water and ethanol, and vacuum dried at 80° C. for 6 h to obtain a modified MOF;

[0080] (4) 1 g of the modified MOF prepared in step (3) was ultrasonically dispersed in 10 mL of deionized water, and the modified MOF dispersion was blended with 3 g of polyacrylamine to obtain a mixed solution (the weight ratio of the modified MOF to the polyacrylamine was 33.33:100), and the mixed solution was scraped onto a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and naturally dried at room temperature for 6 h to obtain CO 2 Separation of mixed matrix composite membranes.

[0081] Comparative Example 1

[0082] 1 g of UIO-66-NH 2 Ultrasonic dispersion was carried out in 10 mL of deionized water, and then UIO-66-NH 2 The dispersion was blended with 6 g of polyethylene amine to obtain a mixed solution (the UIO-66-NH 2The weight ratio of the mixed solution to the polyvinylamine is 16.67:100), the mixed solution is applied on a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and the mixture is dried naturally at room temperature for 6 hours to obtain CO 2 Separation of mixed matrix composite membranes.

[0083] Comparative Example 2

[0084] (1) 1 g of UIO-66-NH 2 Mixing with 2 g of polyethyleneimine in 40 mL of an ethanol aqueous solution containing 50 vol% ethanol, reacting the obtained reaction system at 60° C. for 4 h, centrifuging the obtained reaction product to separate a solid product, washing the solid product with deionized water and ethanol, and vacuum drying at 80° C. for 6 h to obtain a modified MOF;

[0085] (2) 1 g of the modified MOF prepared in step (1) was ultrasonically dispersed in 10 mL of deionized water, and the modified MOF dispersion was blended with 4.33 g of polyvinylamine to obtain a mixed solution (the weight ratio of the modified MOF to the polyvinylamine was 23.08:100), and the mixed solution was scraped onto a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and naturally dried at room temperature for 6 h to obtain CO 2 Separation of mixed matrix composite membranes.

[0086] Comparative Example 3

[0087] (1) 1 g of UIO-66-NH 2 and 0.9751 g of glyoxal (the UIO-66-NH 2 The molar ratio of the amount of glyoxal to the amount of amine groups is 1:4) dispersed in 40 mL of ethanol, 0.128 g of acetic acid (0.4 wt%) was added as a catalyst, and the reaction was carried out at 70° C. for 1 h, the obtained reaction product was filtered and washed with ethanol until there were no obvious impurities, and most of the ethanol was removed by suction to obtain a pre-modified solid;

[0088] (2) 1 g of the pre-modified solid obtained in step (1) was ultrasonically dispersed in 10 mL of deionized water, and the pre-modified solid dispersion was blended with 6 g of polyvinylamine to obtain a mixed solution (the weight ratio of the pre-modified solid to the polyvinylamine was 16.67:100), and the mixed solution was scraped onto a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and naturally dried at room temperature for 6 h to obtain CO 2 Separation of mixed matrix composite membranes.

[0089] Comparative Example 4

[0090] 1 g of MIL-53(Al)-NH 2 Ultrasonic dispersion was carried out in 10 mL of deionized water, and then MIL-53(Al)-NH2 The dispersion was mixed with 11 g of polyethylene amine to obtain a mixed solution (the MIL-53(Al)-NH 2 The weight ratio of the mixed solution to the polyvinylamine is 9.09:100), the mixed solution is applied on a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and the mixture is dried naturally at room temperature for 6 hours to obtain CO 2 Separation of mixed matrix composite membranes.

[0091] Comparative Example 5

[0092] 1g of MIL-101(Cr)-NH 2 Ultrasonic dispersion was carried out in 10 mL of deionized water, and then MIL-101(Cr)-NH 2 The dispersion was blended with 16 g of polyethylene amine to obtain a mixture (the MIL-101(Cr)-NH 2 The weight ratio of the mixed solution to the polyvinylamine is 6.25:100), the mixed solution is applied on a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and the mixture is dried naturally at room temperature for 6 hours to obtain CO 2 Separation of mixed matrix composite membranes.

[0093] Comparative Example 6

[0094] This example was implemented according to the method described in Example 2, except that in step (3), 1 g of the modified MOF prepared in step (2) was ultrasonically dispersed in 10 mL of deionized water, and the modified MOF dispersion was scraped onto a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer, and then naturally dried at room temperature for 6 h to obtain CO 2 Separation of mixed matrix composite membranes.

[0095] Test Example 1

[0096] This test example uses atomic force microscopy to characterize the CO prepared in Examples 1-3 and Comparative Example 1. 2 The morphology and structure of the mixed matrix composite membrane were separated. Figure 1 shown.

[0097] Depend on Figure 1 It can be seen that compared with Comparative Example 1, by adopting the technical solution of the present invention, the CO prepared in Examples 1-3 2 In the separation mixed matrix composite membrane, the MOF material modified by bridging ligands and amine-based polymers has better compatibility with the matrix, thereby improving its CO 2 Separate the loading amount in the mixed matrix composite membrane; at the same time, the prepared CO 2 The wetting effect between the particle surface and the amino polymer in the separation mixed matrix composite membrane is significant, the phase interface is more uniform, and excellent interfacial compatibility is shown.

[0098] Test Example 2

[0099] In this test example, the specific surface area and pore size distribution of the modified MOF materials prepared in Examples 1-5 and Comparative Examples 1-6 were measured by a specific surface area and pore size analyzer to verify the effect of the modification method on the intrinsic properties of the material. The results are shown in Table 1.

[0100] Table 1

[0101]

[0102]

[0103] As shown in Table 1, compared with the MOF raw material, the specific surface area and pore size of the modified MOF prepared in Examples 1-5 decreased slightly, and the decrease in specific surface area and pore size was related to the characteristics of the bridging ligand. This is because the flexibility of the bridging ligands leads to differences in the aggregation state of the grafted polymer on the surface of the nanofiller. The amino polymer with strong positive charge tends to gather around the ligand with strong negative charge in the modified MOF, rather than evenly covering the particle surface, avoiding the pore penetration of the polymer, which is conducive to the construction of high-performance CO 2 Separation of mixed matrix membranes. Compared with Comparative Example 1, the MOF in Comparative Example 2 uniformly and reversibly adsorbed a large amount of amino polymers on the surface through hydrogen bonding, resulting in a significant decrease in specific surface area and pore size, but the compatibility with the amino polymer was improved to a small extent; the MOF in Comparative Example 3 was only modified by a small molecule bridging ligand, which had little effect on its specific surface area and pore size, but the MOF was not modified by the amino polymer, resulting in no significant improvement in compatibility. The above two examples show that both step (1) and step (2) play an important role in maintaining the MOF pore structure and improving the interface compatibility between MOF and the amino polymer, and neither is indispensable.

[0104] Test Example 3

[0105] This test example is used to illustrate the CO prepared in Examples 1-5 and Comparative Examples 1-6. 2 Separation of CO with mixed matrix composite membranes 2 Separation performance. This test case includes the following steps:

[0106] The CO prepared in Examples 1-5 and Comparative Examples 1-6 2 The mixed matrix composite membranes were placed in CO 2 / N 2 Mixed gas (CO 2 With N 2The test was carried out under a system with a volume ratio of 15:85), the feed gas pressure was set to 0.20 MPa, and the test temperature was 25°C. The composition of the permeate gas was analyzed using a gas chromatograph calibrated by an external standard method, and the CO 2 The permeability and separation factor are shown in Table 2.

[0107] Table 2

[0108] Example No. <![CDATA[CO 2 Penetration Rate (GPU)]]> <![CDATA[CO 2 / N 2 Separation Factor]]> Example 1 2034 185 Example 2 1491 148 Example 3 1808 159 Example 4 1583 140 Example 5 2371 134 Comparative Example 1 1269 52 Comparative Example 2 483 129 Comparative Example 3 887 95 Comparative Example 4 568 53 Comparative Example 5 1344 37 Comparative Example 6 / /

[0109] From the results in Table 2, it can be seen that compared with Comparative Examples 1-6, the CO prepared in Examples 1-5 2 Separation of CO with mixed matrix composite membranes 2 Permeability and CO 2 / N 2 The separation factors have been greatly improved, and the CO 2 The permeability is above 1491, CO 2 / N 2 The separation factors are all above 134, showing excellent carbon dioxide selectivity compared with the prior art. 2 Permeability and CO 2 / N 2 The separation factors are lower than those of CO prepared in Examples 1-5. 2 Separation of mixed matrix composite membrane; Comparative Example 6 due to the preparation of CO 2 No amine polymer was added during the separation of the mixed matrix composite membrane, and a uniform and defect-free separation layer could not be formed, so there was no significant CO 2 Separation performance.

[0110] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a mixed matrix composite membrane for CO2 separation, characterized in that: The method comprises the following steps: (1) mixing an amine-containing MOF, a bridging ligand, a first solvent, and an optional first catalyst and performing a first reaction, separating a solid product from the first reaction product to obtain a pre-modified solid; (2) mixing the pre-modified solid obtained in step (1), a portion of the amino polymer, a second solvent and an optional second catalyst to conduct a second reaction, separating a solid product from the second reaction product to obtain a modified MOF; (3) The modified MOF obtained in step (2) is mixed with another part of the amino polymer and coated on a polysulfone ultrafiltration membrane containing a silicone rubber intermediate layer to obtain a CO2 separation mixed matrix composite membrane.

2. The method according to claim 1, characterized in that In step (1), the MOF is selected from at least one of UIO series MOF, MIL series MOF and ZIF series MOF; Preferably, the MOF is selected from at least one of UIO-66-NH2, CAU-1(Al)-NH2, MIL-53(Al)-NH2, MIL-101(Cr)-NH2, MIL-68(In)-NH2, MIL-101(Fe)-NH2, MIL-101(Al)-NH2, MIL-125(Ti)-NH2 and ZIF-8-NH2.

3. The method according to claim 1, characterized in that In step (1), the bridging ligand is selected from at least one of a diepoxy molecule, a dicarboxylic acid molecule and a dialdehyde molecule; Preferably, the bridging ligand is selected from at least one of diepoxybutane, polyethylene glycol diglycidyl ether, oxalic acid, malonic acid, succinic acid, glutaric acid, glyoxal, terephthalaldehyde, glutaraldehyde and 4,4-biphenyldicarboxaldehyde.

4. The method according to any one of claims 1 to 3, characterized in that: In step (1), the molar ratio of the amine group in the MOF to the bridging ligand is 1:2-5.

5. The method according to claim 1, characterized in that In step (1), the first solvent is a polar solvent and / or a polar solvent; Preferably, the first solvent is selected from at least one of water, ethanol, dimethylformamide and tetrahydrofuran; and / or The first catalyst is selected from at least one of acetic acid, formic acid and propionic acid; Preferably, the weight ratio of the first catalyst to the first solvent is 0.01-0.5:

100.

6. The method according to claim 1, characterized in that In step (1), the conditions of the first reaction include: reaction temperature of 40-80° C., and reaction time of 1-6 h.

7. The method according to claim 1, characterized in that In step (2) and step (3), the amino polymer is a branched and / or linear amino polymer; Preferably, the amine-based polymer is selected from at least one of polyethyleneamine, polyethyleneimine and polypropyleneamine.

8. The method according to claim 1, characterized in that In step (2), the weight ratio of the pre-modified solid to the portion of the amino polymer is 1-3:

1.

9. The method according to claim 1, characterized in that: In step (2), the second solvent is an ethanol aqueous solution; Preferably, the concentration of the ethanol aqueous solution is 30-80wt%; and / or The second catalyst is selected from at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide and triethylamine; Preferably, the weight ratio of the second catalyst to the second solvent is 0.01-0.8:

100.

10. The method according to claim 1, characterized in that In step (2), the reaction conditions are: reaction temperature is 30-60°C, and reaction time is 0.5-4h.

11. The method according to claim 1, characterized in that: In step (3), the weight ratio of the modified MOF to the other part of the amino polymer is 30-60:

100.

12. A CO2 separation mixed matrix composite membrane prepared by the method according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Method for preparing mixed matrix membrane for carbon dioxide separation through chemical bridging

    CN109248571A

  • Polyimide / surface-modified metal organic framework mixed matrix membrane as well as preparation method and application thereof

    CN111111459A

  • Method for preparing MOF membrane by seed-assisted supercritical technology and gas separation application thereof

    CN113413778A

  • Nanoreactor for reducing carbon dioxide through acidic electro-catalysis, preparation method and membrane electrode system

    CN114540867A

  • Preparation method of mixed matrix membrane with MOFs (Metal-Organic Frameworks) ordered straight-through channel

    CN115318117A